2020
DOI: 10.1186/s13567-020-00820-x
|View full text |Cite
|
Sign up to set email alerts
|

Sub-lethal doses of albendazole induce drug metabolizing enzymes and increase albendazole deactivation in Haemonchus contortus adults

Abstract: The efficacy of anthelmintic therapy of farm animals rapidly decreases due to drug resistance development in helminths. In resistant isolates, the increased expression and activity of drug-metabolizing enzymes (DMEs), e.g. cytochromes P450 (CYPs), UDP-glycosyltransferases (UGTs) and P-glycoprotein transporters (P-gps), in comparison to sensitive isolates have been described. However, the mechanisms and circumstances of DMEs induction are not well known. Therefore, the present study was designed to find the cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 44 publications
4
17
0
Order By: Relevance
“…In C. elegans , it was shown that the cytochrome P450 Cyp-35d1 is able to oxidise thiabendazole, which is then conjugated to glucose and that downregulation of cyp-35d1 makes worms more susceptible to the effects of thiabendazole on egg laying in both a wild-type and a BZ-resistant, ben-1-deficient genetic background. Both C. elegans and H. contortus have been shown to metabolise several BZs (albendazole, mebendazole, thiabendazole, oxfendazole, fenbendazole and flubendazole) to hexose conjugates [ 70 , 71 , 72 ]. Data about metabolisation of anthelmintic drugs by ascarid nematodes have not been published, but changes in metabolic pathways, such as increased activity, obviously represent another option how anthelmintic resistance might be established in ascarids.…”
Section: Discussionmentioning
confidence: 99%
“…In C. elegans , it was shown that the cytochrome P450 Cyp-35d1 is able to oxidise thiabendazole, which is then conjugated to glucose and that downregulation of cyp-35d1 makes worms more susceptible to the effects of thiabendazole on egg laying in both a wild-type and a BZ-resistant, ben-1-deficient genetic background. Both C. elegans and H. contortus have been shown to metabolise several BZs (albendazole, mebendazole, thiabendazole, oxfendazole, fenbendazole and flubendazole) to hexose conjugates [ 70 , 71 , 72 ]. Data about metabolisation of anthelmintic drugs by ascarid nematodes have not been published, but changes in metabolic pathways, such as increased activity, obviously represent another option how anthelmintic resistance might be established in ascarids.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been suggested that mutations in the isotype 1 gene are not solely responsible, but that BZ resistance may be multi-genic. For example, SNPs in the H. contortus β-tubulin isotype 2 gene have been correlated to BZ resistance in field strains ( Kwa et al, 1993a , 1993b ) and BZ drugs have also been shown to influence the expression of drug metabolizing enzymes and drug efflux pumps ( Beugnet et al, 1997 ; Laing et al, 2010 ; Jones et al, 2013 ; Kellerova et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, some focus on the resistance mechanism turned to XMEs. In H. contortus , researchers have reported a potential role of XMEs in resistance to anthelmintics such as albendazole, which was oxidized in adult worms [ 42 ]. Another study showed that silencing the CYP gene (HCON_00143950), which belongs to a class of XME genes, significantly increased the sensitivity of H. contortus larvae to IVM [ 37 ].…”
Section: Discussionmentioning
confidence: 99%